Liver transplantation and cardiac illness: Current evidences and future directions. (19th February 2020) - Jha, Ajay Kumar; Lata, Suman
Abstract: Contraindications to liver transplantation are gradually narrowing. Cardiac illness and chronic liver disease may manifest independently or may be superimposed on each other due to shared pathophysiology. Cardiac surgery involving the cardiopulmonary bypass in patients with Child–Pugh Class C liver disease is associated with a high risk of perioperative morbidity and mortality. Liver transplantation involves hemodynamic perturbations, volume shifts, coagulation abnormalities, electrolyte disturbances, and hypothermia, which may prove fatal in patients with cardiac illness depending upon the severity. Additionally, cardiovascular complications are the major cause of adverse postoperative outcomes after liver transplantation even in the absence of cardiac pathologies. Clinical decision‐making has remained an unsettled issue in these clinical scenarios. The absence of randomized clinical studies has further crippled our endeavours for a consensus on the management of patients with end‐stage liver disease with cardiac illness. This review seeks to address this complex clinical setting by gathering information from published literature. The management algorithm in this review may facilitate clinical decision making and augur future research. Abstract : Highlight In this review Jha and colleagues explored the pathophysiologic interactions between end‐stage liver disease and cardiac illness. Furthermore, data were extracted from the relevant literature to formulate an appropriate investigation strategy and specific management plan in patients waitlisted for liver transplantation with major cardiac pathologies including coronary artery disease and cardiomyopathy.